The Unintended Consequences of Governance of Education at a Distance Through Assessment and Standardization - Rinne Risto (Springer, 2022)
Governance of education is in transition and education quality represents one key discursive justification for diverse reforms. Transnational actors and commercial interests play a central role in the reform movements. Using data as a technology of governance, quality assurance and evaluation (QAE) is an essential tool for reinforcing central control while at the same time allowing more autonomy to the local actors and agents and creating the need for new experts and data infrastructures. Globalization has been described as resulting in the rescaling of politics and policy, further complicated by the rise of a new mode of governance at a distance through QAE techniques and evaluation data, and the consequent reshuffling of the position of the nation-state and local space. It rests on the provision and translation of information about subjects, objects and processes and brings new limits and possibilities for agents. The new architecture of governance relies on the production and mobility of data. The expanding practices of evaluation produce knowledge about education, which may allow the nation-state to extend its capacity to govern across territory and into the classroom through standardization, commensuration, transparency and comparison and have severe unintended consequences to the behavior of educational agents. Simultaneously, states are increasingly incorporated into the global accountability regime that helps the “national eye” to govern with the “global eye”. Places are the locus where all scales conflate, from the supra-national through to the national and local. There, the educational system becomes “real schools” embedded into a web of multi-scalar and multi-actor relations. The degree of freedom of agents in defining and implementing strategies, taking decisions and accessing resources, relies on those relations, but is never fully determined by them nor straight carry out the intended aims. Most reforms are changing the situations, but also influenced by various educational policies, interest groups, the working of the economy, public meanings, and ways of conceiving the specific issues, evaluation results and other factors. This applies to all aspects, from teacher training, how to handle educational disadvantage or the involvement of other actors. This chapter analyzes the unintended consequences of governance of education at a distance through assessment and standardization to the changes of national and local agents.
Globalisation, Ideology and Education Reforms : Emerging Paradigms